2016
DOI: 10.1038/srep33133
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Thr or Ser Residue Modulates Structural Switches in 2-Cys Peroxiredoxin by Distinct Mechanisms

Abstract: Typical 2-Cys Peroxiredoxins (2-Cys Prxs) reduce hydroperoxides with extraordinary rates due to an active site composed of a catalytic triad, containing a peroxidatic cysteine (CP), an Arg, and a Thr (or Ser). 2-Cys Prx are involved in processes such as cancer; neurodegeneration and host-pathogen interactions. During catalysis, 2-Cys Prxs switch between decamers and dimers. Analysis of 2-Cys Prx structures in the fully folded (but not locally unfolded) form revealed a highly conserved, non-conventional hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 41 publications
4
64
0
3
Order By: Relevance
“…In fact, the analysis of the structure revealed an interaction of the Thr from the active site motif, at the dimer-dimer interface of the decamer. Recently, using different methodological approaches as site-directed mutagenesis, biochemical approaches, size exclusion chromatography, and structural analysis, we have demonstrated that a slight difference in the PXXXT(S)XXC P is involved in decamers to dimers transitions [10]. While Tsa1 possess a Thr residue embedded in the conserved motif, in Tsa2, the Thr is naturally substituted by a Ser (Figure 4).…”
Section: Redox Cycle and Structural Transitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the analysis of the structure revealed an interaction of the Thr from the active site motif, at the dimer-dimer interface of the decamer. Recently, using different methodological approaches as site-directed mutagenesis, biochemical approaches, size exclusion chromatography, and structural analysis, we have demonstrated that a slight difference in the PXXXT(S)XXC P is involved in decamers to dimers transitions [10]. While Tsa1 possess a Thr residue embedded in the conserved motif, in Tsa2, the Thr is naturally substituted by a Ser (Figure 4).…”
Section: Redox Cycle and Structural Transitionsmentioning
confidence: 99%
“…Despite that the basic functional unit of the typical 2-Cys Prx is represented by a α(2) homodimer, studies using the Tsa1 and Tsa2 isoforms from S. cerevisiae revealed that this oligomeric state presents low peroxidase activity, and the highest reactivity of the typical 2-Cys Prx is reached when these proteins are found in a ring-shaped α2(5) decamers (association of five homodimers; Figure 3A). It is believed that the alternation between these two quaternary structures is responsible for the modulation of their peroxidase activity and may be involved in signal transduction ( Figure 3B) [10]. Additionally, the typical 2-Cys Prx enzymes may also present other oligomeric states that will be discussed posteriorly.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations